2018
DOI: 10.1016/j.sapharm.2017.03.055
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with pharmacy students' attitudes towards learning communication skills – A study among Nordic pharmacy students

Abstract: The study provides important information for faculty members responsible for curriculum improvements and teachers to refine their teaching of communication skills. From this, the teaching can be better tailored to suit different students. The students' chances of being able to effectively help patients in the future will be increased by that.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
(127 reference statements)
2
6
0
1
Order By: Relevance
“…This is similar to the findings in the two quantitative Nordic studies, which concluded that student pharmacists in the Nordic countries were not satisfied with the patient directed CST they had received and that students had moderately positive attitudes towards CST [23,24]. Factors associated with positive attitudes towards learning communication skills were a newer pharmacy program, being female, acknowledging a need for improving one’s communication skills and believing one’s communication skills are not the result of personality [24]. Currently the vast majority of research on communication skills and student pharmacists explores their attitudes by applying quantitative research methods [22,24,25,26].…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…This is similar to the findings in the two quantitative Nordic studies, which concluded that student pharmacists in the Nordic countries were not satisfied with the patient directed CST they had received and that students had moderately positive attitudes towards CST [23,24]. Factors associated with positive attitudes towards learning communication skills were a newer pharmacy program, being female, acknowledging a need for improving one’s communication skills and believing one’s communication skills are not the result of personality [24]. Currently the vast majority of research on communication skills and student pharmacists explores their attitudes by applying quantitative research methods [22,24,25,26].…”
Section: Introductionsupporting
confidence: 84%
“…A quantitative American study that measured student pharmacists’ satisfaction with communication teaching methods found that students are more satisfied with nontraditional and non-didactic CST [22]. This is similar to the findings in the two quantitative Nordic studies, which concluded that student pharmacists in the Nordic countries were not satisfied with the patient directed CST they had received and that students had moderately positive attitudes towards CST [23,24]. Factors associated with positive attitudes towards learning communication skills were a newer pharmacy program, being female, acknowledging a need for improving one’s communication skills and believing one’s communication skills are not the result of personality [24].…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Interestingly, when thinking about how cultural awareness and how cultural differences may impact on pharmacy practice, one pharmacist referred to a student who came from another culture. He commended the student for her self-awareness and cultural awareness, both of which are qualities that are highly desirable in Pharmacy students [20,50,51]. Pharmacist 34 explained: “Our student is Egyptian Muslim and she has made us more aware of her Muslim culture and historic background.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that students attitudes toward learning may be influenced by personal characteristics [12][13][14], students' personality traits may play an important role [15]. If personality traits are associated with attitudes toward learning, then the identification and analysis of these traits could support teachers to promote teaching activities…”
Section: Introductionmentioning
confidence: 99%